... = {a_n: n ≥ 1} U {a}. Suppose x ∈

**R**^k \ X. Then x ≠ a and x ≠ a_n for...gt; 2d - d = d > 0, y ≠ a. Therefore y ∈**R**^k \ X. This shows that the open...2 Answe

**r**s · Science & Mathematics · 28/11/2013We need to check that: (1) ∅, ℜ a

**r**e open; (2) T is closed unde**r**... open. Othe**r**wise, U(B_i) = ℜ is open. [[you should check these last two claims...1 Answe

**r**s · Science & Mathematics · 06/02/2013...it has no positive Real roots. When you replace "

**r**" with "-**r**", you get, f(-**r**) = -**r**^5 + 1 and this has one change of...3 Answe

**r**s · Science & Mathematics · 20/02/2014∫ ∫

**r**xy^3 dA**r**: y=x, y=3x, xy=1, xy=4**r**is the**r**egion enclosed by the lines and the hype**r**bolas...1 Answe

**r**s · Science & Mathematics · 29/07/2010Hi impressed voltage = 0 ... Cq +

**R**dq/dt = e(t) q(0) = 0.15 e(t) = 0 Then Cq +**R**dq...1 Answe

**r**s · Science & Mathematics · 23/09/2010S= pi*

**r*** (**r**^2+h^2)^(1/2) a) If neither h nor**r**is a constant, then both dr...and dh/dt will determine how fast the surface area changes. dS/dt = pi***r**[ (1/2)(**r**^2+h^2)^-1/2 * (2r* dr/dt + 2h*dh/dt) ]+ pi*(**r**^2+ h^2)^(1/2)* dr/dt...1 Answe

**r**s · Science & Mathematics · 25/03/2013... that the "subset of" in the definition of

**R**includes improper subsets, the reflexiveness of... consider whether (Q,P) can be in**R**. If so, Qk would have to be a subset of some...1 Answe

**r**s · Science & Mathematics · 09/08/2010...^(n₁) + a₂^(n₂) + ......+ a_

**r**^(n_**r**) whe**r**e n₁ + n₂ + ....+ n_**r**= n.....(1...the context of using the fo**r**mula "n CHOOSE**r**". The**r**e is no cont**r**adiction he**r**e, since we...2 Answe

**r**s · Science & Mathematics · 17/01/2015nPr = n! / (n -

**r**)! 3Pr = 3! / (3 -**r**)! 3! / (3 -**r**)! = 3! 3! = 3! * (3 -**r**)! 1 = (3 -**r**)! n! = 1 when n = 1 or when n = 0. For the sake of ease, let's just say 3 -**r**= 1 3 -**r**= 1 3 - 1 =**r**2 =**r**Pretty much do the same thing for the next...1 Answe

**r**s · Science & Mathematics · 31/05/20153/4(

**r**-1) = 6 Multiply both sides by 4, to get rid of the fraction (4)3/4(**r**- 1) = (4)6 3(**r**- 1) = 24 Use the distributive property to get rid of the ...3 Answe

**r**s · Science & Mathematics · 23/02/2010